2012
DOI: 10.1590/s1984-70332012000400003
|View full text |Cite
|
Sign up to set email alerts
|

Path analysis of iron and zinc contents and others traits in cowpea

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
12
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 12 publications
9
12
3
Order By: Relevance
“…Our results support this association in general, although some genotypes with a smooth testa texture and a large seed size had a shorter cooking time. As Moura et al (2012) suggested that crude protein content and cooking time were not correlated in their analysis with 11 populations, we found no clear correlation in the 20 genotypes. They also reported a negative correlation between crude protein content and grain size, but we found no relationship between crude protein and any grain size parameter in the 240 or 20 genotypes.…”
Section: Discussioncontrasting
confidence: 78%
“…Our results support this association in general, although some genotypes with a smooth testa texture and a large seed size had a shorter cooking time. As Moura et al (2012) suggested that crude protein content and cooking time were not correlated in their analysis with 11 populations, we found no clear correlation in the 20 genotypes. They also reported a negative correlation between crude protein content and grain size, but we found no relationship between crude protein and any grain size parameter in the 240 or 20 genotypes.…”
Section: Discussioncontrasting
confidence: 78%
“…OM, overall mean, ns not significant, **significant at 1%, and 1 value transformed to The low magnitude of g 2 for iron and zinc concentrations indicates the existence of high environmental influence, which makes it more difficult to select iron and zinc concentrations in the cowpea grain, also confirmed by low Snedecor's F values and estimates of g 2 that were not significant (Table 1). The low magnitude of g 2 and high environmental influence for these characters were also found by Moura et al (2012) and Costa (2013), who evaluating cowpea parental and crosses also found low estimates for this parameter.…”
Section: Resultssupporting
confidence: 65%
“…The eight segregating populations were represented by plants in the F 3 (plant)/F 4 (seed) generations, obtained from the BRS Xiquexique x IT-98K-205-8 and BRS Xiquexique x IT-97K-1042-3 crosses (C) and backcrosses (BC) to the BRS Xiquexique parent, including reciprocal ones (Moura et al, 2012). …”
Section: Methodsmentioning
confidence: 99%
“…If the CN is 100-1000, multicollinearity is considered moderate to severe, and if CN ≥ 1000, it is considered severe (Moura et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…The technique, introduced by Wright (1921Wright ( , 1923 and described in detail by Li (1956Li ( , 1975, identifies miscorrelations between two traits that may not necessarily be related by direct cause-andeffect, because of the influence of a third trait. Path analysis has been widely used by plant breeders in a variety of crops, e.g., soybean (Peter et al, 2014), corn (Faria et al, 2015), common bean (Cabral et al, 2011), green bean (Araujo et al, 2012), cowpea (Moura et al, 2012;Santos et al, 2014), rice (Marchezan et al, 2005), wheat (Kavalco et al, 2014), cotton (Hoogerheide et al, 2007;Farias et al, 2016), sweet sorghum (Lombardi et al, 2015), and sugarcane (Saccharum officinarum) (Kang et al, 1983;Reddy and Reddy, 1986;Sukhchain and Sain, 1997;Ferreira et al, 2007;Silva et al, 2009;Souza et al, 2011;Esposito et al, 2012). However, studies of this nature are still necessary, because different population structures, environments, and management strategies should be considered.…”
Section: Introductionmentioning
confidence: 99%